Pengenalan Kosa Kata Bahasa Jepang melalui Mobile Learning Berbasis Game Based Learning - Agus Arifin Wijaya; Saida Ulfa; Henry Praherdiono (Graduate School of Universitas Negeri Malang, 2018)
Abstract: The rapid development of technology and has entered into various community groups one of them is smartphone. As a communication and information tool, smartphones have now turned functionality into a medium that can be used in the learning process. Learning using a smartphone should be able to increase knowledge and become a new way of learning reference. The problem that arises is the limited time students have to learn japanese as the second language used when working in Japan country. The development model used is Lee & Owens development model. The result of this development model is a valid media.Abstrak: Perkembangan teknologi yang cepat dan telah memasuki ke berbagai golongan masyarakat salah satunya adalah smartphone. Sebagai sebuah alat komunikasi dan informasi, smartphone kini telah beralih fungsi menjadi media yang dapat digunakan dalam proses pembelajaran. Pembelajaran menggunakan smartphone haruslah dapat meningkatkan pengetahuan dan menjadi referensi cara belajar baru. Permasalahan yang muncul adalah keterbatasan waktu yang dimiliki siswa untuk mempelajari bahasa Jepang sebagai bahasa kedua yang digunakan saat bekerja di negara Jepang. Model pengembangan yang digunakan adalah model pengembangan Lee & Owens. Hasil model pengembangan ini berupa media yang valid.